Risk factors for immediate and delayed cardiogenic shock in patients with ventricular septal rupture after myocardial infarction - Wang, Si; Zhang, Jing; Xiao, Qian-Feng; Liu, Kai; Xu, Ying; Chen, Xiao-Ping; Wei, Xin; Peng, Yong (Frontiers in Cardiovascular Medicine, 2023)
Background: Ventricular septal rupture (VSR) is a serious complication occurring after myocardial infarction (MI). Cardiogenic shock (CS) is a common complication of VSR and an important factor affecting its prognosis. CS can occur in either an immediate or delayed manner after VSR; however, studies on the risk factors for immediate or delayed CS are scarce. Methods: We retrospectively studied patients admitted to the West China Hospital between September 2009 and August 2023 and diagnosed with VSR after MI. Demographic data, medical history, physical examination results, electrocardiograms, and echocardiographic and hematological data were extracted from electronic medical records or archived records. CS was defined as hypotension (<90 mmHg) and/or the requirement for catecholamines, pulmonary congestion, and signs of end-organ failure. The CS onset time was defined as the time at which catecholamines were initiated. Results: A total of 88 patients with VSR after MI, including 49 males (55.7%), were enrolled. The average age was 70.2 years. Of these patients, 32 (36.4%) who already had CS at the time of VSR discovery were defined as immediate CS, and 28 (31.8%) who developed CS within 2 weeks after VSR discovery were defined as delayed CS. A smaller left ventricular end-diastolic diameter (LVEDD) and VSR discovered after admission were independent risk factors for immediate CS. Elevated heart rate and higher creatine kinase-MB isoenzyme levels on admission were independent risk factors for delayed CS in patients without immediate CS after VSR. Conclusions: The occurrence of CS in patients with VSR after MI has an evident time course. Thus, early identification of patients at risk of immediate or delayed CS and optimization of treatment procedures may help improve the prognosis.